Iliac crest donor site morbidity in patients undergoing anterior cervical discectomy and fusion at Charlotte Maxeke Johannesburg Academic Hospital - Egbunike, Ikechukwu Amaechi (My University, 2020)
Background: Iliac Crest Bone Graft is the gold standard for grafts used in spine surgery. Despite this, there is a decline in its use in Anterior Cervical Discectomy and Fusion (ACDF). This is mainly due to the perceived donor site morbidity associated with its harvesting. The aim of this study was to evaluate iliac crest donor site morbidity in patients undergoing ACDF at a tertiary hospital’s orthopaedic department. The objectives were to (i) determine the incidence of donor site morbidity in these patients, (ii) analyse demographic data pertaining to age and gender, as well as (iii) determine the severity of each adverse effect. Methodology: This was a retrospective study with a prospective recall. Patients who met the inclusion criteria were followed up at the spine unit out-patients department where the study was explained to them and a questionnaire was given to them for completion, after signing an informed consent form. The data were statistically analysed using the IBM SPSS 25 ® software. Results: There were 22 patients who met the study inclusion criteria. Data were stratified into categories. Discussion: None of the study participants experienced any major donor site morbidities, and most of the minor donor site morbidities were self-limiting and resolved timeously. The study compared remarkably well with similar studies done around the world.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020